Answer:
B
Step-by-step explanation:
First, put 3(sqrt(6)) in a different form:
sqrt(9) * sqrt(6) = sqrt(54)
We know that a 30 60 90 triangle has a horizontal leg equal to 1, a vertical leg equal to sqrt(3), and a hypotenuse equal to 2.
Find a multiplier/ratio with this information:
(sqrt(54))/(sqrt(3)) = sqrt(18)
given value/accepted value = multiplier
Now, multiply the other values by the multiplier:
1*sqrt(18) = sqrt(18) or 3(sqrt(2))
2*sqrt(18) = 2(sqrt(18)) or 6(sqrt(2))
Your answer would be:
x = 3(sqrt(2))
y = 6(sqrt(2))
Or option B.